Women's Political Participation in South Waziristan: A Community-Based Survey (Journal of Asian Development Studies, 2024)
This study investigates the impact of political reforms on women's political participation in South Waziristan, Pakistan. The sample consisted of 100 females aged 18 to 45 from the region. The survey was conducted using a self-administered questionnaire, and the Statistical Package (SPSS) was used for the data analysis. The results show a comprehensive knowledge of the current state of political awareness and participation among women in the region, particularly in the context of the 18th Amendment. The study outcome showed significant knowledge about the Amendment's results, which shows a limited impact on women. The majority of respondents (64%) suggested that education initiatives should be implemented to facilitate greater involvement of women in politics. The study focuses on the fact that despite political reforms such as the 18th Amendment, women's political participation in South Waziristan remains limited. This study targeted educational initiatives and community-based efforts to improve political awareness and involvement among women in the region.